2013
DOI: 10.5380/rf.v43i2.29266
|View full text |Cite
|
Sign up to set email alerts
|

VARIAÇÃO LONGITUDINAL E EFEITO DO ESPAÇAMENTO NA MASSA ESPECÍFICA BÁSICA DA MADEIRA DE Mimosa scabrella E Ateleia glazioveana

Abstract: Este trabalho teve como objetivo avaliar a variação longitudinal e o efeito do espaçamento de plantio na massa específica básica das árvores de Mimosa scabrella Benth e Ateleia glazioveana Baill, aos 36 meses de idade. Analisou-se um experimento instalado em delineamento de blocos completos casualizados, com três repetições. Os tratamentos foram definidos em função dos espaçamentos (2,0x1,0 m, 2,0x1,5 m, 3,0x1,0 m e 3,0x1,5 m). Foram avaliadas 72 árvores, sendo essas medidas e cubadas pelo método de Smalian. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…In contrast, Garcia et al (1991) reported a decrease of the BD of the wood with the increase of spacing in wood from E. grandis and E. saligna. For Eloy et al (2013) those differences in the results could be due to several factors, such as genetic variability of the populations and different environmental conditions, based on the different ages.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Garcia et al (1991) reported a decrease of the BD of the wood with the increase of spacing in wood from E. grandis and E. saligna. For Eloy et al (2013) those differences in the results could be due to several factors, such as genetic variability of the populations and different environmental conditions, based on the different ages.…”
Section: Discussionmentioning
confidence: 99%
“…This same trend was verified by Eloy et al (2015), who also did not observe a significant difference in the basic density in Mimosa scabrella wood as a function of planting spacing. However, different spacing influenced the variation in basic density in Mimosa scabrella and Ateleia glazioveana wood, but there was no systematic positive or negative variation in relation to spacing (Eloy et al 2013). In a study with Tectona grandis, Lima et al (2009), they also found that volumetric shrinkage was not influenced by planting spacing.…”
Section: Resultsmentioning
confidence: 95%
“…O mesmo foi verificado por Candaten et al (2018) que no estudo dessa variável, utilizando a espécie Maclura tinctoria (L.) Don ex Steud, encontraram um valor de 1,195 g/cm 3 na base, diminuindo para 1,158 g/cm 3 na região do DAP e aumentando em seguida. Ainda, Eloy et al (2013), também verificaram uma redução da densidade na base até a região do DAP no estudo da espécie de Mimosa scabrella Benth.…”
Section: Resultsunclassified